Gifted Education. The role of ICTs and S.T.E.M., Inquiry - Based Learning - Kefalis, Chrysovalantis (Eximia, 2023)
The aim of this paper is to investigate the relationship between the education of gifted students and S.T.E.M. activities. More specifically, we investigated whether the characteristics of inquiry-based learning (the teaching method that is mainly used in S.T.E.M. education), such as collaboration, exchange of views, complexity, etc., are compatible with the needs and learning preferences of gifted students. Then we explored applications of such activities and their results in gifted education. According to our results, the characteristics of inquiry - based learning are compatible with the preferences of gifted students, while the results of the application of S.T.E.M. activities in the education of gifted children are effective